2019
DOI: 10.3390/antibiotics8040238
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Hydrophilicity and Charge on the Polar Face of Alyteserin 1c Helix Change its Selectivity towards Gram-Positive Bacteria

Abstract: Recently, resistance of pathogens towards conventional antibiotics has increased, representing a threat to public health globally. As part of the fight against this, studies on alternative antibiotics such as antimicrobial peptides have been performed, and it has been shown that their sequence and structure are closely related to their antimicrobial activity. Against this background, we here evaluated the antibacterial activity of two peptides developed by solid-phase synthesis, Alyteserin 1c (WT) and its muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The 3D structural model of SM-985 was predicted using the I-TASSER server, and this model was validated with ProSA-web and MolProbity software. The ProSA-web results showed that the SM-985 3D model was within the favorable region of structures, and these results were comparable to a previous study (Liscano et al, 2019). The results of MolProbity indicated that the peptide structure parameters remained within the limits of acceptable quality and stability (Beg et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…The 3D structural model of SM-985 was predicted using the I-TASSER server, and this model was validated with ProSA-web and MolProbity software. The ProSA-web results showed that the SM-985 3D model was within the favorable region of structures, and these results were comparable to a previous study (Liscano et al, 2019). The results of MolProbity indicated that the peptide structure parameters remained within the limits of acceptable quality and stability (Beg et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…This flexibility in the central region of the peptide reflects a hinge that facilitates contact with the nonpolar region of phospholipids, allowing the peptide to be inserted into the K pneumoniae membrane. 66 In contrast, the peptide remained stable most of the time in the P aeruginosa membrane, except for a slight variation in the amino-terminal end at 3 ns ( Figure 5). Stability is also an important structural property for antibacterial activity.…”
Section: In Silico Interaction Between Camp-cecd and Membrane Models mentioning
confidence: 97%
“…[85]. In contrast, the PAM-18Na-EuCl family, where the complex surface consists mainly of the EuCl polymer (Figure 4), these could interact electrostatically with the bacterial surface, which is rich in anionic phospholipids such as phosphatidylglycerol [86], achieving a membrane-destabilizing effect and allowing the passage of water-soluble molecules [83]. On the other hand, the sizes exhibited by the PECNs (Figure 2) prevents them from entering through the pores of the bacteria cell wall since the latter have sizes between 2.03 and 3 nm [87].…”
Section: Discussionmentioning
confidence: 99%